Analisis Peluang dan Tantangan Pengembangan Agroindustri Kelapa - Suci Wulandari (Agrointek, 2017)
The organization as a pool of resources, capabilities and competencies needed to generate physical products or intangible services which create the competitive advantage. It is developed by effective management of technical aspects and by learning aspects of the organization, and also the influence of an effective networking. How these two factors work to establish value of the organization then effect the degree of competitiveness, is influenced by how much the assets owned by an organization. This value is categorized into tangible and intangible assets. Development of coconut-based products shows a meaningful opportunity in this regard. On the other hand, changes in the global environment have brought changes in the behavior of consumers and competition conditions. Review of the role, coconut commodities provides a great role to the economy nationally. Indonesia is a country with the largest area of coconut production in the world, followed by The Fillippines and India. Exports of coconut products from Indonesia tended to increase. The size of the role and potential of coconut was not followed by the performance of the coconut industry. This is shown by the problems associated with value-added products, linkages, transfer the risks and benefits, the contribution for the development of rural agro-industry, export value of products, industrial competitiveness in medium and small agro-industry in the global market and information flow. Optimizing the value of intangible assets in the system of agro-industry can be improved through the implementation of Knowledge Management occurred through developing external structure, internal structure and individual competency. Application of Knowledge Management refers to the model of two dimensions, namely the process of knowledge creation and innovation, and elements that enable or influence the activities of knowledge creation. This model is implemented by using Knowledge Management Roadmap which consists of 10 steps in 4 phases. Through the implementation of Knowledge Management, coconut agroindustry is expected to become the business units that have optimal value capable of performing competitiveness. Finally, it will satisfy the consumers through on time delivery product, create the customer loyalty which in turn increase the sales growth and gain the result in financial aspects in earning growth